Facilitators and Barriers to Dementia Assessment and Diagnosis: Perspectives From Dementia Experts Within a Global Health Context - Bernstein Sideman, Alissa; Al-Rousan, Tala; Tsoy, Elena; Piña Escudero, Stefanie D.; Pintado-Caipa, Maritza; Kanjanapong, Suchanan; Mbakile-Mahlanza, Lingani; Okada de Oliveira, Maira; De la Cruz-Puebla, Myriam; Zygouris, Stelios; Ashour Mohamed, Aya; Ibrahim, Hany; et al. (Frontiers in Neurology, 2022)
Objectives: Dementia poses one of the greatest global health challenges, affecting 50 million people worldwide. With 10 million new cases each year, dementia is a growing burden, particularly in low- and middle-income countries (LMIC). This study aimed to identify the facilitators and barriers to providing quality dementia assessment and care in LMICs from a global health perspective. Methods/Design: A qualitative semi-structured interview study with 20 dementia expert healthcare providers from 19 countries. To be included, providers had to: practice dementia assessment or care in LMICs where the population over age 60 is projected to more than double by 2050 and be recognized as a leading dementia expert in the region based on position, research publications, and/or policy leadership. Interviews were analyzed by a multidisciplinary team of researchers using thematic analysis. Results: Barriers to dementia assessment and care included stigma about dementia, poor patient engagement in and access to healthcare, inadequate linguistic and cultural validation, limited dementia capable workforce, competing healthcare system priorities, and insufficient health financing. Facilitators included the rise in dementia awareness campaigns, dementia training for general practitioners, availability of family support and family caregivers, and national and international collaborations including coordinated policy efforts and involvement in international research initiatives. Conclusions: Findings from this study provide insights for prioritizing dementia assessment and care capacity-building in LMICs as a global health priority and for tailored public health approaches to strengthen dementia assessment and care at the individual, community, national, and multi-national levels.